Performance evaluation of STANDARD Q COVID‐19 Ag home test for the diagnosis of COVID‐19 during early symptom onset. Issue 6 (20th April 2022) - Shin, Hyoshim; Lee, Seungjun; Widyasari, Kristin; Yi, Jongyoun; Bae, Eunsin; Kim, Sunjoo
Abstract: Background: Surveillance and control of SARS‐CoV‐2 outbreak through gold standard detection, that is, real‐time polymerase chain reaction (RT‐PCR), become a great obstacle, especially in overwhelming outbreaks. In this study, we aimed to analyze the performance of rapid antigen home test (RAHT) as an alternative detection method compared with RT‐PCR. Methods: In total, 79 COVID‐19‐positive and 217 COVID‐19‐negative patients confirmed by RT‐PCR were enrolled in this study. A duration from symptom onset to COVID‐19 confirmation of <5 days was considered a recruiting criterion for COVID‐19‐positive cases. A nasal cavity specimen was collected for the RAHT, and a nasopharyngeal swab specimen was collected for RT‐PCR. Results: Sensitivity of the STANDARD Q COVID‐19 Ag Home Test (SD Biosensor, Korea), compared with RT‐PCR, was 94.94% (75/79) (95% [confidence interval] CI, 87.54%–98.60%), and specificity was 100%. Sensitivity was significantly higher in symptomatic patients (98.00%) than in asymptomatic (89.66%) patients ( p ‐value = 0.03). There was no difference in sensitivity according to the duration of symptom onset to confirmation (100% for 0–2 days and 96.97% for 3–5 days, respectively) ( p ‐value = 1.00). The RAHT detected all 51 COVID‐19 patients whose Ct values were ≤25 (100%), whereas sensitivity was 73.33% (11/15) among patients with Ct values >25 ( p ‐value = 0.01). Conclusion: The RAHT showed an excellent sensitivity for COVID‐19‐confirmed cases, especially for those with symptoms. There was a decrease in sensitivity when the Ct value is over 25, indicating that RAHT screening may be useful during the early phase of symptom onset, when the viral numbers are higher and it is more transmissible.